APPLYING COOPERATIVE LEARNING MODEL TYPE NUMBERED HEAD TOGETHER(NHT) FOR ACCOUNTING STUDENTS AT SMKN 1 NANGA PINOH - Halida Indrasari (Universitas Majalengka, 2020)
Students' low scores and interest in accounting major at SMKN 1 Nanga Pinoh became the main issues in conducting this research. Learning outcomes are low because students are not able to understand the material well. Besides, learning activities were boring for the students. This research aims to improve student learning outcomes in English using the Cooperative Learning Type Number Head Together (NHT) learning model. The research method used was classroom action research. Data collection tools used were observation, test questions, questionnaires, and interviews. The findings showed that in the first cycle, there was a 60% increase in student learning activities, and only 57% of students completed. Meanwhile, more than 50% of the students liked the learning model used. A greater increase was shown by students after the second cycle was implemented. Observation results showed 90% of students were active while studying. Learning outcomes also increase to 90% of students complete. Meanwhile, the response questionnaire shows that almost 100% of students like learning English using the Cooperative Learning Type Number Head Together (NHT) learning model.